A bride's story. 9 - Mori, Kaoru, 1978- (Yen Press, 2017)
Acclaimed creator Kaoru Mori's tale of life on the nineteenth-century Silk Road continues. Pariya's budding romance with Umar is off to a rough start due to her brash personality and lack of confidence. But if she can't figure out how to say what she wants with words, then perhaps the old adage is true--the way to a man's heart is through his stomach!